If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7b + -1) * 33 = 19b Reorder the terms: 2(-1 + 7b) * 33 = 19b Reorder the terms for easier multiplication: 2 * 33(-1 + 7b) = 19b Multiply 2 * 33 66(-1 + 7b) = 19b (-1 * 66 + 7b * 66) = 19b (-66 + 462b) = 19b Solving -66 + 462b = 19b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-19b' to each side of the equation. -66 + 462b + -19b = 19b + -19b Combine like terms: 462b + -19b = 443b -66 + 443b = 19b + -19b Combine like terms: 19b + -19b = 0 -66 + 443b = 0 Add '66' to each side of the equation. -66 + 66 + 443b = 0 + 66 Combine like terms: -66 + 66 = 0 0 + 443b = 0 + 66 443b = 0 + 66 Combine like terms: 0 + 66 = 66 443b = 66 Divide each side by '443'. b = 0.1489841986 Simplifying b = 0.1489841986
| 48-6x=21x+15 | | -4-7q+2q^2=0 | | -44-2x=10x-8x | | 7z+2-3z+5=15 | | F(14)=3(14)+2 | | (2x-5)/9-8(x+3)/3+4=5 | | 3-3x+4x-6=5x+1-x | | 8x-3=5(7-x) | | 6x+6=18-6x | | 2-x/4=1x/6 | | x^8-5=-5 | | (9x-2)/3-1(x+1)/7+3=9 | | 5(2x+1)-9=18 | | 2x+10+30+2x+x/30=360 | | (4x+5)(5x-4)=x+13 | | (2x-3)/2-7(5+2x)/1=4 | | -8x+3=-3x-7 | | 5(y-2)=20 | | 1=4x-5 | | 20=7+5h | | 120+x+3x=360 | | x/5+7=4 | | (5x-2)(5x+2)=25x-7x | | 3k-20=4 | | 2(x+8)-4(x-1)=6 | | x+2/5=3 | | 3x^2=100 | | 7/4w=28 | | 3y+5=2y+8 | | 2y^2+5y-3y=0 | | 6-4y=0 | | 6x+12=2x+6 |